New Description of Evolution of Magnetic Phases in Artificial Honeycomb Lattice. Issue 1 (December 2017) - Summers, B.; Chen, Y.; Dahal, A.; Singh, D.
Abstract Artificial magnetic honeycomb lattice provides a two-dimensional archetypal system to explore novel phenomena of geometrically frustrated magnets. According to theoretical reports, an artificial magnetic honeycomb lattice is expected to exhibit several phase transitions to unique magnetic states as a function of reducing temperature. Experimental investigations of permalloy artificial honeycomb lattice of connected ultra-small elements, ≃ 12 nm, reveal a more complicated behavior. First, upon cooling the sample to intermediate temperature, T T ≃ 175 K, the system manifests a non-unique state where the long range order co-exists with short-range magnetic charge order and weak spin ice state. Second, at much lower temperature, T T ≃ 6 K, the long-range spin solid state exhibits a re-entrant behavior. Both observations are in direct contrast to the present understanding of this system. New theoretical approaches are needed to develop a comprehensive formulation of this two dimensional magnet.